2019
DOI: 10.3390/ijerph16244942
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Rates, Social Capital, and Depressive Symptoms among Older Adults in Japan: An Ecological Study

Abstract: Depression is considered the primary risk factor for older people’s suicide. When considering suicide measures, it is necessary to clarify the relationship between depressive symptoms, social capital, and suicide rates. Therefore, we aimed to clarify the relationship between community-level social capital, depressive symptoms, and suicide rates among older people in Japan. We analyzed the data gathered from 63,026 men and 72,268 women aged 65 years and older, totaling 135,294 subjects in 81 municipalities with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…They showed that the male suicide standardized mortality ratio (SMR) was positively correlated with depressive symptoms (p = 0.002). The female suicide SMR was positively correlated with the rate of depressive symptoms (ρ = 0.258) (38).…”
Section: Mood Disordersmentioning
confidence: 99%
“…They showed that the male suicide standardized mortality ratio (SMR) was positively correlated with depressive symptoms (p = 0.002). The female suicide SMR was positively correlated with the rate of depressive symptoms (ρ = 0.258) (38).…”
Section: Mood Disordersmentioning
confidence: 99%
“…In relation to this, the findings of this study suggest that it may be beneficial to make those supporting public welfare recipients aware that the risk of suicidal behaviour might be elevated in some welfare recipients. More specifically, as the recipients of public welfare are visited regularly by caseworkers it is possible that this ‘intervention’ could be more precisely tailored to function as a form of emotional/social support which has been previously linked to better mental health and reduced suicidal behaviour among older adults in Japan 37. Having said this, as the workload of caseworkers is already heavy in terms of the support they provide for recipients, it is essential that concrete systems/policies be established to promote partnerships between healthcare professionals and welfare offices, as is seen in other settings such as in relation to social prescribing and patient navigation 38 39.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, as the recipients of public welfare are visited regularly by caseworkers it is possible that this ‘intervention’ could be more precisely tailored to function as a form of emotional/social support which has been previously linked to better mental health and reduced suicidal behaviour among older adults in Japan. 37 Having said this, as the workload of caseworkers is already heavy in terms of the support they provide for recipients, it is essential that concrete systems/policies be established to promote partnerships between healthcare professionals and welfare offices, as is seen in other settings such as in relation to social prescribing and patient navigation. 38 39 It is also important to ensure that the actual welfare provided (income) is sufficient enough to guarantee that recipients are not living in poverty or can slip into poverty or experience financial destitution, which may have been a cause of suicidal behaviour 4 5 in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three hundred thirty-five areas have been set up to provide efficient medical services as of January 2021 [5]. Studies on suicide have been conducted at each of the following regional levels: prefectures [6][7][8][9][10][11][12], secondary health care areas [13,14], municipal towns and villages [15][16][17][18][19][20], and cities and villages in specific prefectures [21,22]. It is critical to comprehensively assess the efficiency of suicide prevention measures in each administrative unit, such as prefectures, secondary health care areas, and municipalities, to assure the success of suicide prevention measures throughout Japan.…”
Section: Introductionmentioning
confidence: 99%